Analysis of Differences in Perceptions of Sustainability Knowledge and Sustainability Awareness in the Gender Perspective of Generation Z - Pardede, Silvester Ade Alvino Angelson; Meilasari, Devina; Wirantini, Ni Putu Ayu Regita; Ayu, Maria Sekar; Diva V.W., Maria Angela; Rubiyatno, Rubiyatno (Universitas Bunda Mulia, 2023)
Sustainability has been a hot issue for more than two decades. This issue arises because there is a lot of criticism about environmental damage in various parts of the world which continues to increase yearly. Sustainability knowledge and sustainability awareness are the main focus in promoting the use of sustainability products. Sustainable behavior begins with knowledge and awareness possessed by consumers, both men and women. This study aims to determine the difference between sustainability awareness and sustainability knowledge regarding gender perspective that focuses on Generation Z. This research is quantitative. The sample in this study amounted to 408 Generation Z respondents who knew about sustainable consumption with accidental sampling techniques. The data analysis technique was carried out with a t-test difference test using SPSS version 26. The results showed that there was no significant difference in sustainability knowledge and sustainability awareness between men and women in Generation Z.